Na levada do pandeiro: a música de Jackson do pandeiro entre 1953 e 1967 - Ramos, Manuela Fonsêca (2012)
This research presents an analysis about part of the work of Jackson do Pandeiro, situated between the years of 1953 and 1967. Such analysis aims to point his work as an important exemple of cultural hybridism found in Brazilian music. To better understand this hybridization, pervades our analysis the formation of national and of Northeastern identities that were being built, especially from 1920s. We understand this period of Jackson do Pandeiro‟s work as a contribution to the scaling ideas of Brazilian nationality and of northeasternity , in order to make us comprehend how these formulations of identity are rather part of a historical process, and not a data frozen in time and in static spaces. In this sense, the study is related to a research line of Regional History, since it helps us to comprehend the construction of a specific region, Brasilian Northeast, parting from its relationship with agents and spaces, either national or global ones.